Perception of the pitch and naturalness of popular music by cochlear implant users. (September 2015) - Grasmeder, Mary L.; Verschuur, Carl A.
Abstract : Objectives: To assess the perceived pitch and naturalness of popular music by cochlear implant (CI) users. Methods: Eleven experienced post-lingually deafened adult CI users rated the pitch, naturalness, and clarity of a popular song with 10 frequency allocation settings, including the default. The alternative settings all had logarithmic frequency spacing and frequency shifts of less than one octave compared with the default map. For maps which were perceived as having incorrect pitch, participants adjusted the pitch of the song in real time using a slider, in order to normalize it, and the amount of adjustment was recorded. Results: The default map was rated as having close to correct pitch. Naturalness rating was negatively correlated with basal shift from a baseline logarithmic map, which was the same as the default map for basal electrodes ( R 2  = 0.77). Ratings of the clarity of the lyrics were adversely affected by basal shift. The majority of participants were able to rate and adjust pitch appropriately. The frequency shift in the map was highly correlated with participants' adjustments of the pitch slider ( R 2  = 0.94), but the adjustments were less than expected for the majority of participants. Discussion: The pitch ratings for the default allocation suggest that participants have acclimatized to their processors' frequency allocations. Adjustment of the pitch of the song was possible for the majority and suggested that all but one participant was experiencing frequency compression. Expansion of the frequency allocation might help to alleviate this. Conclusion: Adjustment of the pitch of a popular song could be helpful for tuning CIs.